From Abdulhamid II until Erdoğan: Pan-Islamism Movement in Indonesia and Turkey - Soekarba, Siti Rohmah; Supratman, Frial Ramadhan (Journal Of Middle East and Islamic Studies, 2022)
This paper investigates the relationship between Indonesia and Turkey from nineteenth century until twentieth first century, especially in the are of Erdogan (2002- today) in the framework of Pan-Islamism approach. Pan-Islamism term has been explored by scientists in the Western or non-Western world. Mostly, scientists consider that Pan-Islamism is the act of radical in order to to West domination in Muslim countries. In this paper author argues that Pan-Islamism is not a conservative ideology to expel West domination, but the approach adopted by Muslims in order to adapt with global challenge since nineteenth century. This paper is written from historical approach and based on primary and secondary sources. Ottoman Turkish documents, manuscripts, and Turkish literature played important role to achieve the aim of this paper.